2018
DOI: 10.1080/1553118x.2018.1494181
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Communication as an Emerging Interdisciplinary Paradigm

Abstract: This study explores future directions in strategic communication scholarship by examining the emergence of strategic communication through the lens of interdisciplinary science. The disciplinary status of strategic communication is described through a content analysis of manuscripts published in the International Journal of Strategic Communication since its inaugural issue in 2007 (N = 207).Results reveal positive trends in research productivity, authorship, and globalization of the discipline over an 11-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 40 publications
(40 reference statements)
0
36
0
5
Order By: Relevance
“…The content analysis by Werder et al (2018) reveals that surveys, content analysis, and case studies are the most common methods. It is noticeable that observation is not included among categories of used methods.…”
Section: Methods and Empirical Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The content analysis by Werder et al (2018) reveals that surveys, content analysis, and case studies are the most common methods. It is noticeable that observation is not included among categories of used methods.…”
Section: Methods and Empirical Materialsmentioning
confidence: 99%
“…At the beginning of this article, we refer to the review of articles in IJSC presented by Werder, Nothhaft, Verčič, and Zerfass (2018) and a similar review done by ourselves. These reviews demonstrate the problems with the early development of strategic communication and we highlight some aspects which we find troublesome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the model sketched in Werder et al (2018), and Kuhn's famous theory of scientific revolution (Kuhn, 1996(Kuhn, , 1st edition, 1962, another promising perspective of disciplinary emergence is the four-stage model proposed by Alexander M. Shneider (2009). Complementary to Kuhn's theory, Shneider's model traces how scientific disciplines progress through four evolutionary stages that are not only fundamentally different but require different types of contributors.…”
Section: Shneider's Four-stage Modelmentioning
confidence: 99%
“…As Werder, Nothhaft, Verčič, and Zerfass (2018) argue earlier in this volume, there can be little doubt that strategic communication research fulfills the standard requirements of a discipline: a) a particular object of research; b) a body of accumulated specialist knowledge; c) theories and concepts that organize the accumulated knowledge; d) specific terminologies; e) specific research methods; and, f) some institutional manifestation. The preconference's Call for Papers not only took for granted that strategic communication had "emerged as a global field of communication research" (Nothhaft et al, 2017, p. 1), it also suggested that this global field was going strong.…”
Section: Introductionmentioning
confidence: 97%